2016
DOI: 10.1007/s00423-016-1531-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of fluorescence angiography in a porcine model

Abstract: Perfusion assessment with quantitative indocyanine green fluorescence angiography is not only feasible but easy to perform with commercially available equipment and readily accessible software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 30 publications
2
52
0
Order By: Relevance
“…Ventilation was paused for 10-20 s after injection of ICG to avoid respiratory movement artifacts during the quantification. For quantification, we used previously validated software (q-ICG) [13][14][15][16][17], and a picture of a color-coded output (beta-version of the present system [20]) representing relative perfusion of the segments (Fig. 1).…”
Section: Perfusion Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventilation was paused for 10-20 s after injection of ICG to avoid respiratory movement artifacts during the quantification. For quantification, we used previously validated software (q-ICG) [13][14][15][16][17], and a picture of a color-coded output (beta-version of the present system [20]) representing relative perfusion of the segments (Fig. 1).…”
Section: Perfusion Assessmentmentioning
confidence: 99%
“…Recently, quantitative analysis of ICG-FA (q-ICG) has been introduced to limit the observer bias and reduce reproducibility problems when normal non-quantitative visual ICG-FA is performed. We have previously described our quantification software's validation, reliability, and reproducibility (q-ICG) in a series of animal studies in both normal, increased, and reduced perfusion [13][14][15][16][17].…”
mentioning
confidence: 99%
“…In a porcine model, Nerup et al . reported that the regional blood perfusion of the stomach was significantly associated with both Slope and Fmax 36 . In a small bowel strangulation model, Matsui et al .…”
Section: Discussionmentioning
confidence: 98%
“…The authors described the diversity in perfusion parameters and methodology in the field of gastrointestinal surgery, concluding that the application of ICG-NIRF imaging in this field requires standardization before implementation in a clinical setting. A potential means of achieving standardization is by the process of normalization, a mathematical means of correcting for fluctuations in fluorescence intensity, as yet only described in animal studies with promising results [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%